Оценка устойчивости естественныхи искусственных породных откосов - Шашенко, А.Н.; Ковров, А.С. (Геотехническая механика, 2010)
Виконано аналіз сучасних критеріїв стійкості укосів та бортів кар’єрів. Представлено результати моделювання стійкості борту на кар’єрі Вільногірського ГМК в програмі кінцево- елементного аналізу Phase2 з використанням критеріїв міцності Кулона-Мора, Хоєка-Брауна та Друккера-Прагера. The analysis of up-to-date criteria for open-cast slope stability has been carried out. Results of slope stability modeling at the open-cast of Vilnogirs’k Mining and Metallurgical Plant with specialized finite-element method software Phase2 by Mohr-Coulomb, Hoek-Brown and DruckerPrager failure criteria have been presented.